2014
DOI: 10.4236/ijcm.2014.517136
|View full text |Cite
|
Sign up to set email alerts
|

Update of Aetiological Patterns of Adult Gastric Outlet Obstruction in Accra, Ghana

Abstract: Background: The aetiology of gastric outlet obstruction globally has evolved from benign to malignant causes, but there seem to be no recent data on the trends in Ghana. The aim was, therefore, to identify the current patterns in the aetiology of gastric outlet obstruction in the adult population in Ghana. Methodology: This was a retrospective review of all confirmed cases of gastric outlet obstruction in the last decade, spanning from June 2004 to May 2014, that were managed at the Korle Bu Teaching Hospital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Similarly, Essoun et al reported 55.14% incidence of gastric cancer and 27.10% for PUD as e ologies of GOO involving 107 pa ents. In their study also male pa ents out numbered 10 the female (2.15:1). In another study with 50 cases of GOO, Godadevi et al reported gastric cancer accounted for 52% of 11 cases and PUD 46%.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Essoun et al reported 55.14% incidence of gastric cancer and 27.10% for PUD as e ologies of GOO involving 107 pa ents. In their study also male pa ents out numbered 10 the female (2.15:1). In another study with 50 cases of GOO, Godadevi et al reported gastric cancer accounted for 52% of 11 cases and PUD 46%.…”
Section: Discussionmentioning
confidence: 99%
“…The last several decades have seen a trend toward more cases due to cancer and fewer due to benign causes. [3][4][5][6][7][8][9][10][11][12][13][14] In earlier studies in both developed and developing countries, gastric adenocarcinoma was the most common malignant cause of gastric outlet obstruction. Since then, it has become less common in Western countries, although it remains more common in Asia and Africa.…”
Section: Less Gastric Cancer More Pancreatic Cancermentioning
confidence: 99%
“…Since then, it has become less common in Western countries, although it remains more common in Asia and Africa. [7][8][9][10][11][12][13][14] This trend likely refl ects environmental factors, including decreased prevalence of Helicobacter pylori infection, a major risk factor for gastric cancer, in Western countries. [15][16][17] At the same time, pancreatic cancer is on the rise, 16 and up to 20% of patients with pancreatic cancer develop gastric outlet obstruction.…”
Section: Less Gastric Cancer More Pancreatic Cancermentioning
confidence: 99%